Expression of Features of Socio-Cultural Views in Terms Related to Linguodidactics - Bazarov Ihtiyor (Zien Journals, 2022)
The article deals with the characterization of terminological units from the aspects of lexicosemantic structures which are specific for all their semantic features by means of linguistic approaches. The main semantic properties of terminological units of language didactics can be studied by means of linguistic analysis.
Keywords: Semantic; linguistic; characterization; approaches